2015
DOI: 10.1002/ardp.201400449
|View full text |Cite
|
Sign up to set email alerts
|

MLL Leukemia and Future Treatment Strategies

Abstract: Chromosomal rearrangements of the MLL gene are associated with high-risk infant, pediatric, adult, and therapy-induced acute leukemias. So far, about 80 different direct MLL fusions and about 120 reciprocal MLL fusions have been characterized at the molecular level. The common theme in these leukemia-associated genetic rearrangements is the genetic disruption of the MLL gene. This leads to MLL-X fusion proteins that still bind to nuclear factors (e.g., MEN1, LEDGF), which in turn allow them to target promoters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 31 publications
0
31
0
2
Order By: Relevance
“…These differences may underlie the fact that only MLL1 is involved in chromosomal translocations in leukemia. The mechanisms by which MLL-fusion oncoproteins transform cells have been reviewed extensively [56][57][58][59], but the contribution of the non-translocated, wildtype allele remains controversial. Several early studies suggested that the remaining wild-type MLL1 molecule was required for maintaining MLL-AF9 initiated leukemia or that targeting the HMT activity of MLL1 would be therapeutically beneficial [60,61].…”
Section: Mll1 and Mll2 Functions In Leukemiamentioning
confidence: 99%
“…These differences may underlie the fact that only MLL1 is involved in chromosomal translocations in leukemia. The mechanisms by which MLL-fusion oncoproteins transform cells have been reviewed extensively [56][57][58][59], but the contribution of the non-translocated, wildtype allele remains controversial. Several early studies suggested that the remaining wild-type MLL1 molecule was required for maintaining MLL-AF9 initiated leukemia or that targeting the HMT activity of MLL1 would be therapeutically beneficial [60,61].…”
Section: Mll1 and Mll2 Functions In Leukemiamentioning
confidence: 99%
“…The MLL gene encodes a H3K4 methyltransferase that is critical for development and hematopoiesis. Chromosomal rearrangements involving the MLL gene are associated with high‐risk infant, pediatric, adult and therapy‐induced acute leukemia . To date, over 79 different MLL fusions have been identified in acute leukemia patients .…”
Section: Introductionmentioning
confidence: 99%
“…Chromosomal rearrangements involving the MLL gene are associated with high-risk infant, pediatric, adult and therapyinduced acute leukemia. 4,5 To date, over 79 different MLL fusions have been identified in acute leukemia patients. 6 The most common MLL fusion partners include AF4, AF9, ENL, AF10 and ELL, which together account for over 80% of MLL-rearranged AML 7,8 and 4% of all AML patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, pediatric leukemias with rearrangements involving the promiscuous mixed‐lineage leukemia gene ( MLL ) continue to have a poor outcome. Hence, KMT2A rearrangements ( KMT2A ‐r) remain of great interest because of their wide variety, diverse biological effects, and clinical implications .…”
Section: Introductionmentioning
confidence: 99%